Dietary Diversity and Nutritional Status: An Association Among the Elderly - GL, Kokilaa; Devanbu, Vinoth Chellaiyan; S, Rajeshkannan; A, Aarthy; S, Jerry Alfred; Das, Himadri (National Journal of Community Medicine, 2023)
Background: Old age and nutrition have become a Global challenge. Inadequate dietary intake arises mostly as a result of physiological changes which contribute to malnutrition. Studies conducted in India focused mainly on the Nutritional Status of Infants and Pregnant women, leaving out this important age group which is also vulnerable to malnutrition. The focus of this study was to find out the dietary diversity and its association with nutritional status among the rural elderly. Materials and Methods: This study was a community-based cross-sectional study conducted among 200 elderly participants from twelve selected villages in Chengalpattu district by multistage random sampling. A semi-structured questionnaire obtained from the Food and Agricultural Organization was used to find out Dietary Diversity. Nutritional status was assessed by the Mini Nutrition Assessment tool and Anthropometric indices. The collected data was analysed using SPSS version 21. Results: The mean dietary diversity score was 7.2±1.8. 37% of respondents with dietary diversity scores below the mean value were considered to have Inadequate dietary diversity while 63 % consume diverse diets. Nutritional assessment based on WHO BMI standards revealed undernutrition among 21.5% of respondents while 60% were of normal weight. Chi-square revealed a statistically significant association between Dietary Diversity and Nutritional status (p value=0.000) Conclusion: The present study found that most study participants were consuming a diverse diet and those subjects with better dietary diversity scores had their Body Mass Index in the normal range. This indicates that adequate dietary diversity can contribute to the attainment of optimum nutritional status.